Nylon 6,6/POSS Nanocomposites - Lim, Yi Yu. (2009)
Polyamide 6,6 (PA 66) and octa-amino-phenyl-silsesquioxane (OAPS) were copolymerized via interfacial polymerization to form OAPS/PA 66 nanocomposites. Crosslinking within the OAPS/PA 66 nanocomposites was observed when the samples undergo viscosimetry analysis. The chemical structure of OAPS/PA 66 nanocomposites was characterized by Fourier transform infra-red spectroscopy. Thermogravimetric analysis results showed that increasing OAPS content within OAPS/PA 66 nanocomposites does not enhance oxidative thermal resistance. As observed by differential scanning calorimetry increased in OAPS content results in the increase of glass transition temperature while melting temperature, heat of fusion and degree of crystallinity decreases. Mechanical properties of samples were analyzed using dynamic mechanical analysis and OAPS/PA 66 nanocomposites exhibited lower mechanical properties as compared to neat PA 66.